2019
DOI: 10.1007/s11665-019-04460-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Process Parameters on Plastic Formability and Microstructures of Magnesium Alloy in Single Point Incremental Forming

Abstract: In this paper, using a combination of simulated and experimental results and macroscopic and microscopic observations, we explain the effect of three process parameters: the forming temperature, forming tool radius, and the forming feed rate on the plastic formability of single point incremental forming of AZ31 magnesium alloy sheet in single point incremental forming from macroscopic and microscopic perspectives. The results show that the forming temperature and the tool-head radius strongly affect the macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The size of the grain significantly influences a component's mechanical characteristics. The shear stress between the forming tool and the sheet during the forming process affects grain refinement, and larger forming angles result in smaller grain sizes [40]. The gradually rising formation temperature does not affect grain size [35].…”
Section: Mechanical Behavior Before and After Ph-spifmentioning
confidence: 99%
“…The size of the grain significantly influences a component's mechanical characteristics. The shear stress between the forming tool and the sheet during the forming process affects grain refinement, and larger forming angles result in smaller grain sizes [40]. The gradually rising formation temperature does not affect grain size [35].…”
Section: Mechanical Behavior Before and After Ph-spifmentioning
confidence: 99%
“…The model developed has been observed to predict surface roughness in the incremental forming operation with acceptable dimensional accuracy. Su et al [41] explored the influences of relevant process parameters on the formability of an AZ31 magnesium alloy sheet through SPIF, and they recommended forming tool radius of 5 mm, a forming temperature of 250 o C, and a feed rate of 0.7 mm as the most significant factors. De Castro Maciel et al [42] showed that adhesion on the tool influences the material deformation of magnesium and aluminium alloys during SPIF process when adopting a forming tool with roller ball.…”
Section: Effects Of Process Parameters On Formabilitymentioning
confidence: 99%
“…The model developed was seen to predict surface roughness in the incremental forming process with satisfactory accuracy. Su et al [161] studied the effects of process parameters on the formability of an AZ31 magnesium alloy sheet in SPIF, and they recommended a forming temperature of 250 • C, forming tool radius of 5 mm, and feed rate of 0.7 mm as the most suitable parameters. De Castro Maciel et al [162] observed that adhesion on the tool affects the material deformation of aluminium and magnesium alloys in SPIF when using a roller ball forming tool.…”
Section: Effects Of Process Parameters On Formabilitymentioning
confidence: 99%
“…Tool geometry and tool path Artificial neural network Design of experiments and RSM Friction and lubricants Process parameter optimisation Electro-assisted Joule heating Air-assisted heating Formability is higher for flat tool geometry and climb tool path [147,149,154] Modeling and prediction of formability and process parameters [160,163] Parametric study and optimisation in ISF [10,159,164] Surface finish depends on friction and lubrication conditions [159,167] Optimal parameters for maximum formability [161,163,164] Higher productivity and formability with less forming force [42,48,61,[167][168][169][170][171][172][173][174][175][176] Homogeneous global temperature, orange peel effect [177][178][179][180][181][182][183]…”
Section: Parametric Studymentioning
confidence: 99%